2019
DOI: 10.1007/s11896-019-09339-0
|View full text |Cite
|
Sign up to set email alerts
|

Psychologists and Psychiatrists in Court: What Do They Know About Eyewitness Memory? A Comparison of Experts in Inquisitorial and Adversarial Legal Systems

Abstract: In criminal cases involving eyewitness reports, psychologists or psychiatrists may be recruited as expert witnesses to help triers of facts to evaluate eyewitness statements, on the assumption that psychologists and psychiatrists are real experts, familiar with scientific progress about how memory works. But are they knowledgeable concerning the science of memory? We assessed the knowledge about eyewitness memory of experts from France and Norway, countries having different legal systems, that is: inquisitoria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Researchers have examined legal professionals' knowledge of eyewitness memory in various countries and regions across the world, including China (Jiang & Luo, 2016;, France (Dodier et al, 2019), Italy (Magnussen et al, 2013), Scandinavia (Granhag et al, 2005;Magnussen et al, 2008), and the U.S. (Wise & Safer, 2004). In general, these surveys have found that legal professionals lack sufficient knowledge of important factors that reduce the accuracy of eyewitness testimony, and that the knowledge of legal professionals is not superior to the knowledge of students, lay people, jury or prospective jury members (e.g.…”
Section: Research On Knowledge Of Eyewitness Memorymentioning
confidence: 99%
“…Researchers have examined legal professionals' knowledge of eyewitness memory in various countries and regions across the world, including China (Jiang & Luo, 2016;, France (Dodier et al, 2019), Italy (Magnussen et al, 2013), Scandinavia (Granhag et al, 2005;Magnussen et al, 2008), and the U.S. (Wise & Safer, 2004). In general, these surveys have found that legal professionals lack sufficient knowledge of important factors that reduce the accuracy of eyewitness testimony, and that the knowledge of legal professionals is not superior to the knowledge of students, lay people, jury or prospective jury members (e.g.…”
Section: Research On Knowledge Of Eyewitness Memorymentioning
confidence: 99%
“…This is a slightly lower proportion when compared with the responses of a sample of Norwegian psychologists and psychiatrists, all of whom had previously served as expert witnesses in court (Melinder & Magnussen, 2015). Participants in the current sample were also more uncertain (51%) compared to the psychologists and psychiatrists (14%) surveyed by the current sample of judges was also reported for French psychologists and psychiatrists who regularly serve as expert witnesses in a recent study (Dodier, Melinder, Otgaar, Payoux, & Magnussen, 2019). For the item evaluating beliefs about the repression of adult traumatic memories in perpetrators of murder, a slightly higher proportion of the current sample responded that the perpetrator is lying when compared with the Norwegian psychologists and psychiatrists that had served as expert witnesses (43% and 39%).…”
Section: Discussionmentioning
confidence: 46%
“…For the item evaluating beliefs about the repression of adult traumatic memories in perpetrators of murder, a slightly higher proportion of the current sample responded that the perpetrator is lying when compared with the Norwegian psychologists and psychiatrists that had served as expert witnesses (43% and 39%). A higher proportion of correct responses for this item was observed both in the current sample of judges and the sample of psychologists and psychiatrists with courtroom experience (Melinder & Magnussen, 2015), when compared with French psychologists and psychiatrists (11.7%; Dodier et al, 2019). Although the debate concerning repressed memories continues (see Brewin & Andrews, 2014;McNally, 2017;Otgaar et al, 2019;Patihis, Ho, Tingen, Lilienfeld, & Loftus, 2014), a recent survey found that most memory experts considered it implausible that traumatic memories are often repressed, and also disagreed that repressed memories can accurately be retrieved in therapy (Patihis et al, 2018).…”
Section: Discussionmentioning
confidence: 55%
“…This issue is raised by Goldfarb et al as well: Participants “might have been less cautious if highly inappropriate interview techniques (such as coercion or overly lengthy interviews) were utilized,” and “it may also be that individuals would be more suggestible when incorrect information is conveyed by an authority figure (e.g., police officer)” (p. 392). Moreover, because clinical psychologists—including expert witnesses (Dodier, 2018; Dodier, Melinder, Otgaar, Payoux, & Magnussen, 2019; Melinder & Magnussen, 2015)—may endorse erroneous beliefs about how memory works, such as the belief in repressed memories (Magnussen & Melinder, 2012; Patihis, Ho, Tingen, Lilienfeld, & Loftus, 2014), they might misinterpret victims’ stated details and/or miss factors known to influence memory. Therefore, using a CI to facilitate memory retrieval would be relevant, if not needed, for both forensic (i.e., investigative interview) and clinical (i.e., psychology and/or psychiatry expert testimony, psychotherapy) purposes.…”
Section: The Forensic Relevance Of Investigative Interviewingmentioning
confidence: 99%